The Repurchase Intention in Handcrafted MSEs: The Mediating Role of Customer Satisfaction in the Relationship between Customer Experience and Product Value - Harwida, Gleydis; Novilia, Evita (Universitas Ciputra Surabaya, 2026)
Micro and Small Enterprises (MSEs) in the handcrafted industry play an important role in supporting local economic development; however, they often face challenges in maintaining long-term customer relationships in increasingly competitive markets. This study aims to examine the factors influencing repurchase intention among consumers of handcrafted MSEs by analyzing the roles of customer experience and product value, with customer satisfaction acting as a mediating variable. This research adopts a quantitative explanatory approach using survey data collected from 140 consumers who have purchased handcrafted MSEs products. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS–SEM). The results indicate that customer experience and product value significantly influence repurchase intention. Both variables also have a significant positive effect on customer satisfaction, which in turn significantly affects repurchase intention. Furthermore, the mediation analysis reveals that customer satisfaction partially mediates the relationships between customer experience and product value with repurchase intention. The model demonstrates adequate explanatory power, indicating that the proposed variables are important predictors of consumer repurchase behavior. These findings contribute to the marketing literature in the MSEs context and provide practical insights for handcrafted MSEs owners to enhance customer satisfaction through improved customer experience and stronger product value to encourage repeat purchases and support business sustainability.